Descriptions and validation of the names of some high-rank syntaxa in the European Asplenietea trichomanis and Polypodietea - Mucina, Ladislav; Theurillat, Jean-Paul (Lazaroa, 2015)
The paper presents the description of one new order (Asplenietalia septentrionalo-cuneifolii) and two new alliances (Arenarion bertolonii and Physoplexido comosae- Saxifragion petraeae). In addition, the syntaxon Asplenietalia lanceolato-obovati is here formally raised to the order level and the name Hypno-Polypodietalia vulgaris is validated.